Pedagogy of praxis : a dialectical philosophy of education - Gadotti, Moacir (State University of New York Press, 1996)
Annotation One of the foremost Brazilian philosophers of education presents some of his ideas, focusing on people, their actions, and their consciousness. He begins with the premise that human history is the product of people's struggle against inequality, which he describes in terms of a dialectic of oppositions and a pedagogy of consciousness. Dialectics for Gadotti is both a means of inquiry and the textual and dynamic foundation of human and cultural evolution. Annotation copyright by Book News, Inc., Portland, OR.
Keywords: Education -- Philosophy.; Dialectic.; Critical pedagogy -- Philosophy.; Pragmatism.; Educational equalization -- Philosophy.; Éducation -- Philosophie.; Dialectique.; Pédagogie critique -- Philosophie.; Pragmatisme.; Démocratisation de l'enseignement -- Philosophie.; dialectic.; pragmatism.; EDUCATION -- Philosophy & Social Aspects.; Critical pedagogy -- Philosophy; Dialectic; Education -- Philosophy; Educational equalization -- Philosophy; Pragmatism; Dialektische Pädagogik; Erziehungsphilosophie; Kritische Pädagogik; Onderwijs.; Filosofische aspecten.; Kritische pedagogiek.